Konsumentbeteende: En studie av hur konsumenter påverkas av kvantitet i priserbjudanden - Hallerfors, Anna (2014)
Consumers daily meet the retail marketing of various products, since all marketers want to reach out to their consumers in the best way. In this thesis the aim is to investigate how the framing of a decision task affects consumer choice, with a focus on consumers initial information processing. The experiment consisted of a slide show of 20 pairs of pictures, in which 45 students at Luleå University of Technology participated. The subjects’ task was to estimate all the deals in the slideshow in terms of their attractiveness. The hypothesis was that consumers find a sales promotion, which contains several items as more attractive than an offer with only one larger object, even though the price and quantity of goods is the same. The result show a significance and, hence, the hypothesis was verified. The differences seen in the subjects' initial information processing are explained by the so called rules of thumb, such as the reference point, the anchoring effect, and representativeness. Validerat; 20140602 (global_studentproject_submitter)